Sub-surface measurements of the austenite microstructure in response to martensitic phase transformation. (15th October 2019) - Bucsek, Ashley; Seiner, Hanuš; Simons, Hugh; Yildirim, Can; Cook, Phil; Chumlyakov, Yuriy; Detlefs, Carsten; Stebner, Aaron P.
Abstract: In this work, we measure the microstructure response of the austenite phase during martensitic phase transformation tens of micrometers beneath the surface of a bulk single crystal nickel-titanium shape memory alloy. Using an emerging dark-field X-ray microscopy (DFXM) technique, the austenite phase fraction, relative misorientation, and elastic lattice plane strain are measured in the interior of the microstructure with a spatial resolution of 108 nm. The results show that some defects consistently induce forward transformation and delay reverse transformation, while other defects consistently impede the propagation of both forward and reverse transformation fronts. We also show that the austenite undergoes an orientation splitting wherein the austenite near the transformation front is constrained from rotating and the austenite far from the transformation front is free to rotate. Finally, we measure interfacial strain fields at the transformation front that extend tens of micrometers into the material. We use an analytical model to show how these strain fields can be explained by a lack of kinematic compatibility between the austenite and martensite phases at the austenite-martensite interface. Graphical abstract: Image 1